Innu and Naskapi materials, Collection of Canadian Indian linguistic materials - Vegreville, Rev. Pere, Oblate of Mary Immaculate (1876)
Dictionnaire Montagnais-francais, from copy at Catholic University of America. Alphabetical list of stems (by Montagnais), 51 pages. Vocabulary without order, 29 pages, and verb conjugations, 29 pages.